(untitled) (Fiep Bulletin - online, 2014)
In Viçosa - MG, the recyclable materials collectors perform their activities in precarious conditions of safety, being exposed to several dangerous situations which lead them to a bad quality of life (QOL) and health. With the intention of transforming that reality, the present work aimed to implement a program of guided physical activities seeking the improvement of the QOL and health of these workers. The work was organized in three stages, with a sample of 30 individuals. In the first stage, a diagnosis of the subjects’ profile, quality of life as well as complaints of muscular pain was accomplished. The results were: age between 24 and 66; 60% of women and 40% men; formal education from 1 to 11 years; working day of 5 to 12 hours; monthly wages between R50,00 and R500,00; 13.3% consider his/her QOL neither bad nor good; 83.3%, good and 3.3% very good; the collectors had pains in the thighs, calves, articulation of elbows and shoulders, which were more frequent and intense in the spine, stomach area and knees. In the second stage, a program of guided physical activities was implemented to reduce the muscular pains, care for the psychological well-being, improve social relationships and teamwork. In the third stage, we intended assess the impact of the program implemented. We concluded that the regular practice of a physical activity has a positive influence in the life of the collectors, lessening muscular pain and fatigue, improving mood and self esteem, stimulating socialization and increasing disposition for work, thus contributing to the improvement of the QOL and health. And, to the researcher (the Physical Education student), participating in rescuing the dignity of that group and applying and assessing the knowledge acquired during her course aided her in strengthening the pillars of her education.